Physiological response and impact of COVID-19 pandemic among Malaysian citizens: a cross-sectional study - Gunawardana, Nalini Anukshi; Md Roduan, Mohd Rohaizad; Ezani, Eliani; Saidi, Hasni Idayu; Muhamad Zakuan, Noraina; Nurdin, Armania (Universiti Putra Malaysia Press, 2024)
Introduction: Studies have shown that staying at home for prolonged periods of crisis can pose a significant challenge to individuals and affect their mental health. Hence, this study was conducted to identify the susceptible subgroups among Malaysian citizens that are prone to mental health problems during the lockdown period of the COVID-19 pandemic and its association with sociodemographic factors. Methods: The mental health status was assessed using the Depression, Anxiety, and Stress Scale -21 (DASS-21) questionnaire. The survey link was distributed online between October and December 2020. Results: Of 637 respondents, one-third experienced mild to extremely severe depression and anxiety (31.1 and 35.1, respectively). Female respondents (odds ratio = 1.516, 95 confidence interval (CI) 1.057-2.172) were 1.5 times more likely to experience mild to severe depression than male respondents. Unmarried and divorced respondents were 2.1 times more prone to experience mild to severe depression than married respondents. A significant association was also found between employment status and age with depression symptoms among the respondents. For anxiety, a significant association was observed between the age group with mild to severe anxiety symptoms. Marital status, age, and employment status were socio-demographic factors significantly impacting stress levels. Conclusion: According to our findings, females, individuals aged 18-30 years old, students, unmarried and divorced respondents were more susceptible to mental health problems, suggesting that mental health support shall also be provided for these vulnerable groups during the COVID-19 crisis.